2019
DOI: 10.1177/0963689719893950
|View full text |Cite
|
Sign up to set email alerts
|

Screening Hub Genes as Prognostic Biomarkers of Hepatocellular Carcinoma by Bioinformatics Analysis

Abstract: Hepatocellular carcinoma (HCC) is a widespread, common type of cancer in Asian countries, and the need for biomarker-matched molecularly targeted therapy for HCC has been increasingly recognized. However, the effective treatment for HCC is unclear. Therefore, identifying additional hub genes and pathways as novel prognostic biomarkers for HCC is necessary. In this study, the expression profiles of GSE121248, GSE45267 and GSE84402 were obtained from the Gene Expression Omnibus (GEO), including 132 HCC and 90 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 51 publications
12
71
0
Order By: Relevance
“…Research found that RRM2 was a novel downstream target activated by HPV E7, and promoted angiogenesis by producing ROS, activating the ERK1/2 signaling pathway and inducing expression of HIF-1a and VEGF, leading to cervical angiogenesis and carcinogenesis [6]. At present, evidence of the relationship between RRM2 and CDKN3 in cervical cancer is limited, but their relationship can be found in other cancers, such as hepatocellular carcinoma, breast cancer, renal carcinoma and lung cancer [51][52][53][54]. Qi et al have found RRM2 and CDKN3 may become biomarkers for diagnosis and poor prognosis of breast cancer [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research found that RRM2 was a novel downstream target activated by HPV E7, and promoted angiogenesis by producing ROS, activating the ERK1/2 signaling pathway and inducing expression of HIF-1a and VEGF, leading to cervical angiogenesis and carcinogenesis [6]. At present, evidence of the relationship between RRM2 and CDKN3 in cervical cancer is limited, but their relationship can be found in other cancers, such as hepatocellular carcinoma, breast cancer, renal carcinoma and lung cancer [51][52][53][54]. Qi et al have found RRM2 and CDKN3 may become biomarkers for diagnosis and poor prognosis of breast cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al have found RRM2 and CDKN3 may become biomarkers for diagnosis and poor prognosis of breast cancer [51]. Zhou et al have also found there is a correlation between RRM2 and CDKN3 in hepatocellular carcinoma [52]. Wei et al found RRM2 and CDKN3 associated with the metastasis of Clear cell renal cell carcinoma [53].…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory network of circRNA-miRNAs-mRNAs and hub genes was constructed using Cytoscape software 3.6.0 [11,12]. The CytoHubba application, a Cytoscape plugin, was used to select hub genes [13].…”
Section: Target Gene Prediction and Regulatory Network Constructionmentioning
confidence: 99%
“…In the past, studies focusing on analysis of HCC-related genes usually included patients with HCC caused by various factors such as chronic hepatitis B or C virus infection and alcoholic liver disease [18,19,34]. But there is limited research that only discusses HCV-related liver cancer on the background of HCV-cirrhosis, so we re-analyzed the data in GSE6764.…”
Section: Disscusionmentioning
confidence: 99%
“…Now, there are rich public repositories of RNA-seq and microarray datasets, such as Gene Expression Omnibus (GEO) database [16] and The Cancer Genome Atlas (TCGA) [17]. Further analysis of those datasets combined with computational approach such as prediction model can provide the opportunity to establish a novel biomarker for disease diagnosis with high accuracy [18,19].…”
Section: Introductionmentioning
confidence: 99%